Letter to Editor - -, - (Pakistan Journal of Ophthalmology, 2018)
Pakistan Journal of Ophthalmology aims to improve quality and standard of the journal to promote research in the field of Ophthalmology and in this regard PJO invites our valuable readers to submit Letter to Editor with their ideas, suggestions and positive scientific criticism with reference not more than 300 words long for possible publication within one month. Pakistan Journal of Ophthalmology reserves the right to edit letters and may publish them in upcoming issues in print and electronic media (website). Submission of a letter implies consent for publication unless otherwise indicated in the letter. All letters must include the correspondent’s name and address and are subject to editing to meet style, clarity, and space requirements. We shall highly appreciate if letters may be sent to pjoosp@gmail.com. Please include “Letter to Editor" in the subject line and address your typed letter to: Editor, OSP House, 4-A LDA Flats Lawrence Road, Lahore- Pakistan. Please include your name and address.